2020
DOI: 10.20944/preprints202010.0395.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Way Forward To Promote The Farming Contracts Between Firms And Farmers In Cultivation Productions: A CASE STUDY Of VIETNAM

Abstract: In an age of market liberalization, globalization, and expanding agribusiness, there is a danger that small-scale farmers will find difficulty in fully participating in the market economy. One of the solutions to solve the above situation is to strengthen linkages between farmers and firms through contract farming. The purpose of this study is to assess the factors affecting the level of linkages between businesses and farmers in crop development in Thai Binh province, Vietnam. The two main research methods us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Very limited studies considered studying the Vietnamese exports of agricultural products, including coconut [17,18]. Moreover, most of the literature related to agricultural exports in SEA or Vietnam present papers focusing on a single perspective of export competitiveness and success, as in supply chain [18,19]), quality management and pricing [20], consumers' preferences [21], accession to World Trade Organization [22], trade relations with European union and the U.S.A as a target market [23,24], government involvement [25], and consideration of organic cultivation [26]. Moreover, most of the research studies approaching the topic focus on aggregate data sources of production [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Very limited studies considered studying the Vietnamese exports of agricultural products, including coconut [17,18]. Moreover, most of the literature related to agricultural exports in SEA or Vietnam present papers focusing on a single perspective of export competitiveness and success, as in supply chain [18,19]), quality management and pricing [20], consumers' preferences [21], accession to World Trade Organization [22], trade relations with European union and the U.S.A as a target market [23,24], government involvement [25], and consideration of organic cultivation [26]. Moreover, most of the research studies approaching the topic focus on aggregate data sources of production [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review indicates that the main motivation of farmers toward the rice contract farming (RCF) schemes are better output market, supportive benefits for the production, and better performance of rice farming [7], while the factors affecting farmers' participation are commitment, sharing of benefits and risks, household awareness about the benefits of contracts, policy environment, management skills and enterprises capacity of link firms, and price issues [8]. Other studies revealed the perception of specific factors affecting participation such as risk perception and perceived credit uncertainty [9,10].…”
Section: Introductionmentioning
confidence: 99%